High-temperature thermal stability and axial compressive properties of a coaxial carbon nanotube inside a boron nitride nanotube - Liew, K M; Yuan, Jianhui (Nanotechnology, 2011)
The structural performance of double-walled C(5, 5)@BN(10, 10) and C(5, 5)@C(10, 10) nanotubes subject to high temperatures is investigated through molecular dynamics simulations. It is found that the inner tube C(5, 5) in the C(5, 5)@BN(10, 10) exhibits less distortion than that in the C(5, 5)@C(10, 10) at annealing temperatures of 3500 and 4000 K. The C(5, 5)@BN(10, 10) and C(5, 5)@C(10, 10) models with different axial compressive strains are optimized using the universal force field (UFF) method. It is found that the critical buckling strains of the inner tubes in the C(5, 5)@BN(10, 10) and C(5, 5)@C(10, 10) are 12.74% and 9.1%, respectively. The critical buckling strain of the former is larger than that of the latter; although the former exhibits greater deformation and energy loss after buckling than does the latter. These phenomena are also analyzed on the basis of the radial distribution function (RDF) and system energy. The results of this study indicate that the outer tube boron nitride nanotube (BNNT) has a better protective effect on the inner tube than does the outer tube carbon nanotube (CNT) under both high-temperature and lower compressive strain conditions. In these cases, the thermal stability and compressive resistance properties of the C(5, 5)@BN(10, 10) are superior to those of the C(5, 5)@C(10, 10).